Off our backs : a women's newsjournal. (Washington : Off our backs, 1982)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks (behalve aug.-sep.)
Redactie : 2337 B18th St., NW Washington, DC 20009
Engels
Krant